Vitamin D decreases cell death and inflammation in human umbilical vein endothelial cells and placental explants from pregnant women with preeclampsia cultured with TNF-α - Nunes, Priscila Rezeck [UNESP]; Romao-Veiga, Mariana [UNESP]; Ribeiro, Vanessa Rocha [UNESP]; de Oliveira, Larissa Ragozo Cardoso [UNESP]; Zupelli, Thiago Gameiro [UNESP]; Abbade, Joelcio Francisco [UNESP]; Peracoli, Jose Carlos [UNESP]; Peracoli, Maria Terezinha Serrao [UNESP] (Taylor & Francis, 2021)
This study evaluated the impact of vitamin D on Human Umbilical Vein Endothelial Cells (HUVEC) and inflammation in placental explants from women with preeclampsia (PE). HUVEC and explants from 10 late-onset PE (LOPE), 10 early-onset (EOPE), and 10 normotensive (NT) pregnant women were cultured with/without tumor necrosis factor (TNF-α) and VD. Interleukin-1β (IL-1β), 18 (IL-18), TNF-α, and TNF-related apoptosis-inducing ligand (TRAIL) were detected by ELISA. High mobility group box 1 (HMGB1) was determined by qPCR/Western blotting, and cell death by flow cytometry. Statistical significance was accepted at p < .05. Compared to the NT group, the endogenous levels of IL-1β, TNF-α, and IL-18 were higher in the PE group. The stimulus with TNF-α increased cytokines in NT, TNF-α in EOPE/LOPE, IL-18 in LOPE, and all cytokines in HUVEC. TNF-α+VD treatment decreased cytokines in explant and HUVEC supernatants. TRAIL was higher in EOPE versus NT, while TNF-α increased this receptor in NT versus control. In HUVEC, TNF-α increased TRAIL versus control, and TNF-α+VD decreased levels compared to only TNF-α stimulus. Protein expression of HMGB1 was higher in explant cultures treated with TNF-α and decreased after TNF-α+VD treatment in all groups, and gene/protein expression in HUVEC. Gene expression was elevated in EOPE versus NT and LOPE, and TNF-α increased HMGB1 in NT versus control, while TNF-α+VD decreased mRNA levels in EOPE. TNF-α stimulus increased late apoptosis in HUVEC, while VD increased viability. These in vitro observations suggest that VD administration to women with preeclampsia may be beneficial in reducing placental inflammation and cell death.
Keywords: Cell death; HUVEC; placental explants; preeclampsia; TNF-α; vitamin D